If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -1d) = 2 + 4d (5 * 2 + -1d * 2) = 2 + 4d (10 + -2d) = 2 + 4d Solving 10 + -2d = 2 + 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. 10 + -2d + -4d = 2 + 4d + -4d Combine like terms: -2d + -4d = -6d 10 + -6d = 2 + 4d + -4d Combine like terms: 4d + -4d = 0 10 + -6d = 2 + 0 10 + -6d = 2 Add '-10' to each side of the equation. 10 + -10 + -6d = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -6d = 2 + -10 -6d = 2 + -10 Combine like terms: 2 + -10 = -8 -6d = -8 Divide each side by '-6'. d = 1.333333333 Simplifying d = 1.333333333
| q+d=19 | | 2x+8=6-5x | | 1/3(5-x)=6 | | -4(b+5)=-b+7 | | 12y-7y=18 | | y=5x-2-3x+5 | | 6/2x15 | | 8(u+4)-4(u+9)=8 | | 90=3(6x-6) | | 9m+7=5m+27 | | 5(f-1)=15 | | 6z=(0.5z-8) | | -96=2-7(2-4n) | | 4(2y+1)-7y=18 | | 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 | | 5p-2q=23 | | 3(4s+4)=7 | | 4/3x3.14x343= | | 6(2l+2)=132 | | -1+3(7+3x)=83 | | 7m-3+2m=13+m | | sinx=1.5 | | 13x+5y=179 | | 25=40+3x | | 6(21+2)=132 | | 144=6(5x+4) |